Prevalence, trend, and predictor analyses of vitamin D deficiency in the US population, 2001–2018 - Cui, Aiyong; Xiao, Peilun; Ma, Yuzhuo; Fan, Zhiqiang; Zhou, Fengjin; Zheng, Jiang; Zhang, Liang (Frontiers in Nutrition, 2022)
ABSTRACT Background The National Health and Nutrition Examination Surveys (NHANES) continuously collected and publicly released data every two years. The latest data on vitamin D from NHANES (2015–2016 and 2017–2018 two cycles) have not been used to investigate the vitamin D status in the United States. Meanwhile, whether the prevalence of vitamin D deficiency has decreased is unclear. We aim to analyze trends and predictors of vitamin D status in the US population with the data from NHANES (2001–2018). Methods Using the most recent data from NHANES (2001–2018) with 71,685 participants, we estimated the prevalence of serum 25(OH)D level of < 25, 25–50, 50–75, and > 75 nmol/L in Americans. We also described trends of vitamin D status from 2001 to 2018. Age-specific prevalence of serum 25(OH)D level < 25, 25–50, 50–75, and > 75 nmol/L were multiplied by the UN World Population Prospects data to estimate the number of cases with different serum 25(OH)D levels in 2025. Weighted multivariate linear regression models were used to explore the predictors of vitamin D deficiency and insufficient. Results The weighted prevalence of serum 25(OH)D level < 25, 25–50, 50–75 and > 75 nmol/L was 2.6%, 22.0%, 40.9%, and 34.5%, respectively. The prevalence of vitamin D deficiency and insufficiency was higher in female, Non-Hispanic Black, people aged 20-29 years, and winter. From 2001 to 2018, a slight linear decline was found in serum 25(OH)D levels of 25–50 (P=0.009) and 50–75 nmol/L (P=0.014). However, no trend change was found in serum 25(OH)D level < 25 nmol/L (P=0.698). The estimated number of cases with serum 25(OH)D levels of < 25, 25–50, and 50–75 nmol/L would be around 7.4, 62.4, 123.1 million in 2025, respectively. Conclusion Vitamin D deficiency is still highly prevalent in the United States, especially in Non-Hispanic Black, female, individuals aged 20–29 years, and winter. Individuals, healthcare providers, and policymakers should take public health measures to developing and implementing prevention strategies for vitamin D deficiency.